Masculinity and Class in the Context of Dirty Work. Issue 2 (5th January 2016) - Slutskaya, Natasha; Simpson, Ruth; Hughes, Jason; Simpson, Alexander; Uygur, Selçuk
Abstract : Through an ethnographic study of 'dirty work' (refuse collection and street cleaning), this article explores how masculinity and class intersect — how, in a mutually constitutive sense, they produce attitudes and practices, strengths and vulnerabilities, which are shaped by shifting relations of privilege and power. We find resistance to class subordination through adherence to traditional forms of masculinity and through esteem‐enhancing social comparison (e.g., with women; with migrant workers). Men also mobilized powerful nostalgic themes around the loss of traditional jobs as well as trade union power. We argue that displays of masculine resilience in the face of devaluation are less indicative of a culture of masculine dominance but more an expression of vulnerability and social dislocation, serving both as a source of resistance whilst simultaneously reinforcing anchors of social disadvantage that characterize forms of dirty work. We suggest that combining social comparison with intersectionality can potentially highlight how categories of difference are strategically deployed in response to varied and unequally valued social positionalities.